Highly selective and dual responsive test paper sensor of Hg2+/ Cr3+ for naked eye detection in neutral water - Das, Priyadip; Ghosh, Amrita; Bhatt, Hitesh; Das, Amitava (RSC Advances, 2012)
A highly selective and sensitive colorimetric and fluorogenic sensor (L1) for Hg2+/Cr3+ is reported. This reagent (L1) was synthesized by reacting 4-((4 (dimethylamino)phenyl)diazenyl)benzene-1-sulfonyl chloride, which has a dimethylaminophenyldiazenyl fragment as a photoactive signalling unit, with 2,2′-(3,3′-azanediylbis(propane-3,1-diyl))diisoindoline-1,3-dione as the receptor fragment. The reagent was characterized by standard analytical and spectroscopic techniques. Electronic spectral studies revealed that the reagent was selective for Hg2+ and Cr3+ in the presence of all other metal ions of Group 1A, IIA and all other common transition metal ions. On binding of L1 to the Hg2+ or Cr3+ centres, a new intense absorption band with a λmax of 509 nm appeared with associated changes in the visually detectable solution colour from yellow to red. Fluorescence spectral studies revealed a significant enhancement in the emission intensities upon coordination to Hg2+ or Cr3+ without any change in the emission wavelength. This could be explained by the efficient interruption of the photo induced electron transfer signalling mechanism involving an unshared pair of electrons from the central tertiary amine centre. An easy to prepare paper test kit, which was obtained by soaking the filter paper in a dichloromethane solution of L1, presents an approach that could be successfully used in the detection of Hg2+ or Cr3+ ions present in neutral aqueous media. This indicates the potential application of this dip strip type sensor for the detection of Hg2+ and Cr3+ in neutral aqueous environments without any spectroscopic instrumentation. Importantly, this reagent binds specifically to Cr3+ in the presence of an excess of iodide ions, which act as a masking agent for Hg2+. To the best of our knowledge, there are very few examples of detection limits lower than the present test strip for Hg2+ in the literature, while, for Cr3+, no such report is available.